Application of the Cox Proportional Hazard Model on Survival Data of Multiple Myeloma Patients Using the R Application - Riyan, Achmad; Nengsih, Surya (Indonesian Council of Premier Statistical Science, 2025)
Multiple Myeloma is a type of blood cancer characterized by the proliferation of malignant plasma cells in the bone marrow and can affect the patient's survival. This study aims to analyze the influence of age, sex, and protein levels on patient survival time. Multiple Myeloma uses the Cox Proportional Hazards model. The data used came from 47 patients with variables of survival time, patient status (dead or alive), age, gender, and protein content. The analysis was carried out using R software. The model match test with the likelihood ratio test also showed insignificant results, but testing of the assumption of proportional hazards through residual Schoenfeld showed that all variables met the model's assumptions. Thus, the Cox PH model in this study is technically valid, but its predictive power is still limited, so further model development is recommended by increasing the amount of data or considering other more relevant variables.